Factors Associated with the Incidence and Severity of New-Onset Atrial Fibrillation in Adult Critically Ill Patients. (15th June 2017) - Duarte, Péricles A. D.; Leichtweis, Gustavo Elias; Andriolo, Luiza; Delevatti, Yasmim A.; Jorge, Amaury C.; Fumagalli, Andreia C.; Santos, Luiz Claudio; Miura, Cecilia K.; Saito, Sergio K.
Abstract : Background . Acute Atrial Fibrillation (AF) is common in critically ill patients, with significant morbidity and mortality; however, its incidence and severity in Intensive Care Units (ICUs) from low-income countries are poorly studied. Additionally, impact of vasoactive drugs on its incidence and severity is still not understood. This study aimed to assess epidemiology and risk factors for acute new-onset AF in critically ill adult patients and the role of vasoactive drugs. Method . Cohort performed in seven general ICUs (including cardiac surgery) in three cities in Paraná State (southern Brazil) for 45 days. Patients were followed until hospital discharge. Results . Among 430 patients evaluated, the incidence of acute new-onset AF was 11.2%. Patients with AF had higher ICU and hospital mortality. Vasoactive drugs use (norepinephrine and dobutamine) was correlated with higher incidence of AF and higher mortality in patients with AF; vasopressin (though used in few patients) had no effect on development of AF. Conclusions . In general ICU patients, incidence of new-onset AF was 11.2% with a high impact on morbidity and mortality, particularly associated with the presence of Acute Renal Failure. The use of vasoactive drugs (norepinephrine and dobutamine) could lead to a higher incidence of new-onset AF-associated morbidity and mortality.